Non-tuberculous cutaneous mycobacterioses, - Lais Bastos Nogueira; Carina Nogueira Garcia; Marcela Santos Corrêa da Costa; Monica Brauner de Moraes; Patrícia Shu Kurizky; Ciro Martins Gomes (Sociedade Brasileira de Dermatologia, 2021)
Abstract Non-tuberculous mycobacteriosis, previously known as atypical, anonymous, opportunistic, or unclassified mycobacteriosis, refers to pathogenic mycobacterioses other than those caused by Mycobacterium tuberculosis and Mycobacterium leprae. These mycobacteria are known for their environmental distribution, mainly in water and soil. The incidence of non-tuberculous mycobacteriosis has been increasing in all countries and skin infections are being increasingly studied, mainly with the increase in immunosuppressive conditions and the development of new medications that affect immunological function. In the present article, a detailed narrative review of the literature is carried out to study the main non-tuberculous mycobacteriosis that cause diseases of the skin and appendages. The article also aims to present a historical context, followed by epidemiological, microbiological, and clinical characteristics of these diseases. Practical considerations about the diagnosis and treatment of non-tuberculous mycobacteriosis are detailed.